Upfront Radiotherapy with Concurrent and Adjuvant Vismodegib Is Effective and Well-Tolerated in a Patient with Advanced, Multifocal Basal Cell Carcinoma - Abigail I. Franco; Gary Eastwick; Ramsay Farah; Marvin Heyboer; Mijung Lee; Paul Aridgides (Case Reports in Dermatological Medicine)
We present a case report of a male with multifocal and extensive basal cell carcinoma. Due to extremely large size and deep tumor infiltration, he was not a surgical candidate. Combined modality treatment of fractionated radiation with concurrent vismodegib was chosen. Concurrent treatment was previously reported in the palliative and recurrent setting. This is the first case of concurrent vismodegib and radiation therapy for upfront definitive management. The patient experienced complete response in all treated lesions.